PENDIDIKAN ISLAM SEBAGAI UPAYA MENGOPTIMALKAN POTENSI MANUSIA - Amaly, Abdul Mun?im; Rizal, Ahmad Syamsu; Supriadi, Udin (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract: Education today is a concern because many people (students) do not maximize the potential they have from the education they have done so that it appears from various circles to implement Islamic education, but is it true that Islamic education is able to produce the people expected? The purpose of this study is to reveal how Islamic education can optimize the full potential of humans. By using qualitative methods and literature study methods, researchers explore, review several documents and literature both journals, books, articles and other readings with analysis of description and interpretation of data. This analysis shows that Islamic education is a necessity for humans. In this case, humans need education, especially Islamic education. With Islamic education, humans are not only able to maximize their potential, but education can direct and guide humans to become better and better personalities and to use their potential properly and even be able to shape humans as the most perfect creatures that can continue to change according to various changing times and the environment that is happening. Keywords: Human, Islamic Education, Human Potential